Teachers’ Strategies In Teaching Reading Skills During Offline Learning In Post Covid-19 Pandemic Period - Nadian, Rera; Afifi, Nur (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2023)
The convenience of online learning during the covid-19 pandemic period has left lingering effects to the post-covid face to face learning making offline learning in the class a difficult task that sometimes demotivates the students. This problem has a lot of influence on student’s learning process of various subjects, one of them was an English reading class. The teachers are demanded to be creative by employing interesting and attractive strategies to keep the student engaged during the class. Teacher’s strategies will help the students in gaining, maintaining and honing their reading skills. This study aimed to portray the challenges faced during the offline learning post covid pandemic period and the strategies employed by the teachers to overcome the challenges. The design of this research is descriptive qualitative. The data on challenges and strategies were obtained through observation and interview from two English teachers in the tenth grade of the school. The data then was analysed following qualitative data analysis by identification, categorization and drawing conclusion followed by triangulation to ensure the validity of the analysis. The results showed that the challenges faced by the teachers in the class were on the following matter: attendance, building motivation, sharing the lesson, vocabulary, reading skills. The attendance challenge was approached by knowing more about the students and the reasons of their absence. Other challenges were approach by employing various teaching techniques such as apperception, brainstorming, giving feedback and employing videos in the teaching learning process